The effect of particle size on radiation shielding properties for bismuth borosilicate glass - W. Cheewasukhanont (2020)
© 2020 Elsevier Ltd The aim of this work is to study the radiation shielding properties of size dependent bismuth in sodium calcium borosilicate glasses. The Bi2O3 in these glasses have the particle size in micrometer (M-BNCBS) have been compared the radiation shielding properties with the glasses that replaced the Bi2O3 with Bi nano-powder (N-BNCBS). The results show that the density of M-BNCBS and N-BNCBS is higher at higher concentration of Bi and the particle size of Bi does not affect to the density of glasses. The molar volumes increase with Bi content and show the higher in N-BNCBS with relative different increase with Bi content due to the NBOs more created. The N-BNCBS have the values of mass attenuation coefficients, effective atomic numbers and electron densities higher than M-BNCBS due to the larger electron cloud density in N-BNCBS. The half value layer of N-BNCBS found to be less than M-BNCBS. These results show that the particle size will affect the radiation shielding properties. Moreover, the radiation shielding properties of these glasses found to be better than Commercial window glass and some standard shielding concrete when compared.